Pertanggungjawaban Pidana Notaris atas Pembuatan Akta yang Memuat Keterangan Palsu dan Akibat Hukumnya - Aktanotaria, Ade; Halim, Anriz Nazaruddin; Chandra, Tofik Yanuar (AKADEMIK: Jurnal Mahasiswa Humanis, 2025)
Notarial deeds are designed to serve as strong legal evidence, ensuring certainty and preventing disputes. However, in practice, deeds sometimes contain false statements, raising questions about their legal consequences and the extent of notary liability. This study aims to examine the criminal liability of notaries who intentionally include false information in authentic deeds and to analyze the resulting legal impacts. The research applies a normative juridical method, using a legislative and case approach. Legal materials were collected through statutory analysis, literature, academic journals, and relevant judicial decisions, then examined by grammatical and systematic interpretation. The findings reveal that deeds containing false information are legally null and void. If proven to have acted intentionally, notaries may be held criminally liable under the Indonesian Penal Code, particularly Articles 263 and 266, with penalties including imprisonment. In addition to criminal sanctions, notaries may also face civil liability for unlawful acts and administrative sanctions such as suspension or dismissal imposed by supervisory authorities. This research highlights the importance of strengthening prudential principles, ethical compliance, and supervisory mechanisms to safeguard the integrity of the notarial profession and ensure legal certainty.